Design inspirations - Books, Daab. (London : daab, 2007)
Technological developments, social and global trends and issues influence the current projects and work approach of designers. Also materials and production methods have never had a bigger influence on up-to-date design than in the age of nanotechnology and biopolymers. Nowadays objects are not regarded purely esthetic anymore, the functionality of design will gain more and more importance in the future. This fourth volume of the Inspiration series offers a comprehensive overview of projects and products of international designers on over 700 pages. This extremly fascinating and inspiring mix portrays the latest developments in a captivating and informative manner. The book is divided into the chapters: furniture, household, industrial design, lighting and textiles. An index with contact information of the designers and architects is enclosed.
Keywords: Industrial design